Once and for all : a novel - Dessen, Sarah (New York : Viking, 2017)
Is it really better to have loved and lost? Louna's summer job is to help brides plan their perfect day, even though she stopped believing in happily-ever-after when her first love ended tragically. But charming girl-magnet Ambrose isn't about to be discouraged now that he's met the one he really wants. Maybe Louna's second chance is standing right in front of her.
Keywords: Families -- Juvenile fiction; Teenagers and death -- Juvenile fiction; Young adult fiction; Romance fiction